2018
DOI: 10.1186/s13023-018-0876-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and outcome in infantile Sandhoff disease: a case series of 25 patients from Iranian neurometabolic bioregistry with five novel mutations

Abstract: BackgroundInfantile Sandhoff disease (ISD) is a GM2 gangliosidosis that is classified as a lysosomal storage disorder. The most common symptoms of affected individuals at presentation are neurologic involvement. Here we report clinical course and demographic features in a case series of infantile Sandhoff disease. Enzymatically and some genetically proven cases of ISD were extracted from the Iranian Neurometabolic Registry (INMR) in Children’s Medical Center, Iran, Tehran from December 2010 to December 2016.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 17 publications
(24 reference statements)
0
22
0
Order By: Relevance
“…Upon activation, astrocyte secretes the chemokines CCL2 and CXCL10 which is consistent with a robust microglial activation as wells as an invasion of peripheral immune cells. It could allow the degeneration of myelinating oligodendrocytes and its death, promoting active demyelination [89,90], which is frequently observed in infantile forms of GM2 gangliosidosis [4,91,92]. Together, these findings highlight the pivotal interplay between microglia and astrocytes in the inflammatory response observed in the GM2 gangliosidosis, which could be the functional consequence of neuronal injury due to GM2 ganglioside accumulation contributing to the neurodegenerative process.…”
Section: Neural Death and Neuroinflammationmentioning
confidence: 84%
See 1 more Smart Citation
“…Upon activation, astrocyte secretes the chemokines CCL2 and CXCL10 which is consistent with a robust microglial activation as wells as an invasion of peripheral immune cells. It could allow the degeneration of myelinating oligodendrocytes and its death, promoting active demyelination [89,90], which is frequently observed in infantile forms of GM2 gangliosidosis [4,91,92]. Together, these findings highlight the pivotal interplay between microglia and astrocytes in the inflammatory response observed in the GM2 gangliosidosis, which could be the functional consequence of neuronal injury due to GM2 ganglioside accumulation contributing to the neurodegenerative process.…”
Section: Neural Death and Neuroinflammationmentioning
confidence: 84%
“…Using this approach, the authors found that ICV administration of the chimeric enzyme on SD mice allowed a significant reduction of GM2 ganglioside in the brain (77%) and cerebellum (57%), compared to untreated SD mice. Likewise, a 2-fold increase in Hex activity and a marked reduction of GM2 ganglioside was observed in liver; which could have a Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 7 July 2020 doi:10.20944/preprints202007.0137.v1 significant impact on the disease [111], since, unlike to TSD, hepatosplenomegaly can be found in SD patients [92].…”
Section: Current Proposals For the Treatment Of Gm2 Gangliosidosismentioning
confidence: 99%
“…Upon activation, astrocyte secretes the chemokines CCL2 and CXCL10, which correlates with a robust microglial activation and the invasion of peripheral immune cells. This astrocytes activation could lead to degeneration and death of myelinating oligodendrocytes, promoting active demyelination [ 84 , 85 ], which is frequently observed in infantile forms of GM2 gangliosidoses [ 4 , 86 , 87 ]. Together, these findings highlight the pivotal interplay between microglia and astrocytes in the inflammatory response observed in GM2 gangliosidoses, which could be the functional consequence of neuronal injury due to GM2 ganglioside accumulation and that may contribute to the neurodegenerative process.…”
Section: Physiopathology Of Gm2 Gangliosidosesmentioning
confidence: 99%
“…This approach, led to a significant reduction of GM2 ganglioside in the brain and cerebellum and a 2-fold increase in Hex activity. Noteworthy, a marked reduction of GM2 ganglioside was also observed in liver; which could have a significant impact on the disease, since hepatosplenomegaly is a common clinical finding of SD patients [ 87 ]. Together, these results suggest that ICV ERT is a potential strategy for the treatment of GM2 gangliosidoses and that N-glycans modifications may have a positive effect on enzyme uptake, biodistribution, and substrate reduction throughout the brain.…”
Section: Current Proposals For the Treatment Of Gm2 Gangliosidosesmentioning
confidence: 99%
“…The blood samples from patient was collected and spotted on filter paper and placed in 3 mm diameter. After addition of elution liquid and substrate solution then incubate of the samples at 37°C , the enzyme activity quantified by comparing the amount of hydrolyzed product with a calibrator [17] [18].…”
Section: β-Hexosaminidase Activity Assaymentioning
confidence: 99%